Perancangan Sistem Transmisi Data Kesehatan Mobil Menggunakan DHT22 - Wiko, Bimo; Muayyadi, Achmad Ali; Armi, Nasrullah (eProceedings of Engineering, 2024)
The design of a data transmission system for monitoring vehicle health is highly relevant to the advancement of modern automotive technology, particularly in enhancing driving safety through the detection of potential hazards and rapid response to emergency situations. Vehicles equipped with various sensors, such as caliper temperature, engine temperature, vehicle emissions, and transmission temperature, generate data that can be integrated to improve the intelligence and performance of the vehicle. This intelligent data transmission system is designed to monitor vehicle conditions in real-time, provide accurate information, and facilitate anomaly detection, thereby reducing traffic accidents caused by vehicle malfunctions or abnormal conditions. Testing has shown that the system functions effectively, with average transmission temperatures of 28℃ when idle and 70℃ when moving, engine temperatures of 54℃ when idle and 81℃ when moving, and caliper temperatures of 27℃ when idle and 31℃ when moving. Vehicle emissions were recorded at 946 ppm when idle and 1235 ppm when the vehicle was in motion. Further development should focus on managing the temperature of the ESP32 microcontroller, ensuring sensor durability in various conditions, and enhancing the device's longevity. Additionally, adding sensors and improving the software to monitor additional health parameters are necessary to increase efficiency and user-friendliness, making this system a crucial contribution to maintaining vehicle health and safety in the future. Keyword: Blynk, Health, Microcontroller, Monitoring, Sensor.